Spring into Technical Writing for Engineers and Scientists - Rosenberg, Barry J. (Addison-Wesley, 2005)
The fastest way for professionals to master technical writing! You’re a technical professional, perhaps a programmer, engineer, or scientist. You are not a professional writer, but writing is part of your job (specs, manuals, proposals, lab reports, technical presentations, Web content, data sheets, and so on). Welcome. This book is for you. It’s all you need to clearly communicate technical ideas to any audience—technical or nontechnical—and motivate them to act.